Prick and intracutaneous testing and IgE testing - Mahler, Vera (Kanerva's Occupational Dermatology, 2019)
Immediate-type allergies are frequent in specific occupational environments. Most important is to consider the possibility of occupational factors in allergic diseases. Depending on the substance, immunological and nonimmunological mechanisms may be relevant for symptom elicitation. According to European Directive 2001/83/EC in vivo test allergens are medicinal products, whereas test allergens for in vitro use are medical devices following respective regulations. Standardized test preparations for in vivo and/or in vitro testing for specific IgE to occupational allergen sources are rare. False-negative as well as false-positive test reactions may occur with current test methods for detection of specific IgE to occupational allergen sources. Compared to ubiquitous inhalant allergens (cut-off = 3.00 mm wheal diameter), for occupational allergens, a different cut-off (wheal diameter = 1.5 mm) applies. Skin prick testing, intracutaneous testing and in vitro investigation of specific IgE constitute one component in a stepwise assessment for diagnosis of allergen-induced occupational diseases. High- and low-molecular-weight allergens have to be considered as occupational allergen sources in specific work environments.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Componentresolved diagnosis; Contact urticaria; Diagnostic algorithm; Exposures; Intracutaneous test; Intradermal test; Molecular allergy diagnostics; Occupational/work-related thinitis/asthma; Skin prick test; Specific igE; Type I Allergy